Development of Android-Based Learning Media Using App Inventor to Improve Student’s Learning Outcomes for Dynamic Fluid Materials - Triyadi, Almer Zahran; Amarulloh, Reza Ruhbani (Jurnal Penelitian Pembelajaran Fisika, 2024)
Technology plays a great role in education, particularly in facilitating creative and innovative approaches to physics learning. This study focuses on developing Android-based learning media using App Inventor for dynamic fluid materials. This Research and Development (R&D) was based on the Jan Van Den Akker model. The development stages covered preliminary research, needs analysis, prototyping, summative evaluation, and reflection and documentation. Data on the effectiveness and practicality of the developed media were obtained from questionnaires distributed to experts, teachers, and students. Data were analyzed using N-Gain tests and obtained a score of 0.63 which is in the moderate category. The developed learning media has a high level of effectiveness in improving students’ understanding of dynamic fluid materials. The results of this study indicate the potential to expand the application of technology in learning to improve quality and sustainable innovation in physics learning.